Bioefficacy of cadmium and lead on cotton leafworm Spodoptera littoralis (Lepidoptera: Noctuidae) larvae. Issue 1 (2nd January 2017) - Eesa, Naeem M.; El-Sherif, Hanaa; El-Sayed, Wael M.; Abd El-Monem, Dina H.
Abstract: The sensitivity of Spodoptera littoralis second and fourth instar larvae to the heavy metals cadmium (Cd) and lead (Pb) was investigated under laboratory conditions. Both Cd and Pb, even, at very low concentrations, had relatively high toxic effects on S. littoralis larvae. Cd was more toxic to S. littoralis larvae than Pb. In addition, the mean percentage feeding deterrence (FDI%) of Cd and Pb was concentration-dependent. The nutritional indices (consumption index, growth rate, efficiency of converted ingested and digested food, and approximate digestibility) of S. littoralis second and fourth instar larvae were more affected in Cd-treatments compared with those of Pb-treatments. Therefore, the presence of such heavy metals in the environment would exert an adverse impact on S. littoralis larvae and their development.